The H i bias during the Epoch of Reionization. Issue 4 (18th October 2019) - Xu, Wenxiao; Xu, Yidong; Yue, Bin; Iliev, Ilian T; Trac, Hy; Gao, Liang; Chen, Xuelei
ABSTRACT: The neutral hydrogen (H i ) and its 21 cm line are promising probes to the reionization process of the intergalactic medium (IGM). To use this probe effectively, it is imperative to have a good understanding on how the neutral hydrogen traces the underlying matter distribution. Here, we study this problem using seminumerical modelling by combining the H i in the IGM and the H i from haloes during the epoch of reionization (EoR), and investigate the evolution and the scale dependence of the neutral fraction bias as well as the 21 cm line bias. We find that the neutral fraction bias on large scales is negative during reionization, and its absolute value on large scales increases during the early stage of reionization and then decreases during the late stage. During the late stage of reionization, there is a transition scale at which the H i bias transits from negative on large scales to positive on small scales, and this scale increases as the reionization proceeds to the end.